Complex vestibular macular anatomical relationships need a synthetic approach. - Ross MD (Acta Oto-Laryngologica (Supplement))
Mammalian vestibular maculae are anatomically organized for complex parallel processing of linear acceleration information. Anatomical findings in rat maculae are provided in order to underscore this complexity, which is little understood functionally. This report emphasizes that a synthetic approach is critical to understanding how maculae function and the kind of information they conduct to the brain.